2022
DOI: 10.4082/kjfm.21.0102
|View full text |Cite
|
Sign up to set email alerts
|

Serum Low-Density Lipoprotein Cholesterol Levels and Depressive Mood in Korean Adults: A Nationwide Population-Based Study

Abstract: Background: The association between serum cholesterol levels and depression has been studied extensively; however, results are inconsistent. This study aimed to investigate the association between low-density lipoprotein cholesterol (LDL-C) levels and depressive symptoms among Korean adults.Methods: This cross-sectional study used data obtained from the 2007–2015 Korea National Health and Nutrition Examination Survey. In total, 40,904 adults were included in the final analysis. Participants were categorized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It is possible that the correlation between depression and LDL-C levels followed a U-shaped pattern, as indicated by previous research. [10] Depression is linked to either elevated or reduced levels of LDL-C, to put it differently. Another reason is that the traditional CVD risk factors may serve as mediators in the relationship between depression and hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the correlation between depression and LDL-C levels followed a U-shaped pattern, as indicated by previous research. [10] Depression is linked to either elevated or reduced levels of LDL-C, to put it differently. Another reason is that the traditional CVD risk factors may serve as mediators in the relationship between depression and hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Rubina et al recently conducted a study which found that there was no correlation between depression and low levels of LDL-C in adult Indians. [9 ] In a cross-sectional study of 40,904 Korean adults, it was discovered by scientists that depression symptoms are linked to either low or high levels of LDL-C. [10] In Northern Mexican Population, depression was significantly linked to lower cholesterol levels according to a different study. [11] According to a meta-analysis conducted by Persons et al, [12] there is a correlation between decreased LDL-C levels and an increased likelihood of experiencing depression.…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol has a crucial role in brain development and in neuron-to-neuron signaling [22]. Past studies showed that low-density lipoprotein (LDL) cholesterol levels are associated with depression [23][24][25]. LDL cholesterol can reduce the availability of serotonin and increase depression risk [26] by directly impairing the function of the serotonin 1A receptor in the brain.…”
Section: Discussionmentioning
confidence: 99%